2012
DOI: 10.1007/s10805-012-9154-7
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Students’ Decisions to Report Cheating: A Laboratory Experiment

Abstract: We use a controlled laboratory experiment design to test rational choice theory on student whistleblowing. We examine reporting costs by comparing actual reporting behavior under anonymous and non-anonymous reporting channels. Reporting benefits are explored by considering the influence on reporting of group versus individual reward systems. We find that the type of reporting channel does not significantly influence student reporting behavior. Rewarding students based on group test scores results in significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…An investigation into this phenomenon by Trevino and Victor (1992) found that students were generally more supportive and inclined to report another’s cheating behavior when a curved grading criterion was presented, and the dishonest act was likely to have a negative impact on themselves and others in the class. In Jenkel and Haen’s (2012) experimental study, students were twice as likely to report the confederate’s cheating behavior when the grading criterion was curved compared with when it was absolute. While there is evidence to suggest that different grading scenarios affect students’ peer reporting tendencies, its influence on another type of reaction that students’ might have upon seeing a peer cheat (i.e., direct confrontation) has yet to be determined.…”
Section: Factors That Influence Students’ Peer Reporting Behaviormentioning
confidence: 94%
See 1 more Smart Citation
“…An investigation into this phenomenon by Trevino and Victor (1992) found that students were generally more supportive and inclined to report another’s cheating behavior when a curved grading criterion was presented, and the dishonest act was likely to have a negative impact on themselves and others in the class. In Jenkel and Haen’s (2012) experimental study, students were twice as likely to report the confederate’s cheating behavior when the grading criterion was curved compared with when it was absolute. While there is evidence to suggest that different grading scenarios affect students’ peer reporting tendencies, its influence on another type of reaction that students’ might have upon seeing a peer cheat (i.e., direct confrontation) has yet to be determined.…”
Section: Factors That Influence Students’ Peer Reporting Behaviormentioning
confidence: 94%
“…Based on the previous work of Vaughn et al (2009), it was hypothesized that relatively few students would report information voluntarily (i.e., before being questioned) or in response to one of the three open-ended questions. However, given the findings of Jenkel and Haen (2012), it was expected that the majority of students would peer report when asked direct questions about the incident.…”
Section: The Current Studymentioning
confidence: 99%
“…Hence, students may sometimes refrain from reporting cheating because other concerns seem more important, not because they disregard the value of academic integrity. Existing research on students' reasoning about reporting is limited, and most previous studies have either tested explanatory factors pre-determined by the researchers (Jenkel & Haen, 2012;Pupovac et al, 2019) or obtained qualitative responses from small focus groups (Rennie & Crosby, 2002). The present research used open-ended interview prompts and manipulated scenarios in surveys to examine the considerations influencing students' decisions about whether to report.…”
Section: How Do Students Decide Whether To Report Cheating?mentioning
confidence: 99%
“…The relatively simple scenarios tested in the present research identified specific factors that mattered in students' decisions to report (e.g., personal involvement in the situation, severity of cheating act), which can be combined to capture the complexity of decisions in realistic situations. Building on methods that test decisions to report in experimental settings (Jenkel & Haen, 2012;Yachison et al, 2018), future extensions of this research can investigate whether students' predictions align with their decisions in academic contexts.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Reasons for reporting include avoiding negative consequences for themselves or others, maintaining standards and integrity, getting violators the help they need, and satisfying the desire for vengeance. Jenkel and Haen (2012) suggested that one way to encourage reporting is to make sure students understand how cheating by their peers affects their own grade. They also suggested a reporting system must maintain anonymity in order to reduce social costs and fear of reprisal.…”
Section: Preventionmentioning
confidence: 99%